THE RELATIONSHIP BETWEEN FAMILY SUPPORT AND THE READINESS OF THE MENARCHE IN YOUNG WOMEN - Etika Purnama Sari (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2020)
Background: Sexual maturity in young women is characterized by menarche. The changes occurring at the moment of the menarche cause teenagers to become awkward. Therefore, teenagers need to organize behavioural adjustments that require family support, especially parental support.Objectives: The purpose of this research is to analyse the family support relationship with the readiness of menarche in young women.Design: The design of this research is non-experimental with correlation methods and cross sectional approaches.Methods: The population of this study is all students of 5th and 6th grade Elementary School, Taman Belajar Surabaya who have not had a menstrual period of 40 students. Sampling techniques use simple random sampling. Large sample of 36 respondents. Collection of data using a family support questionnaire and a target readiness questionnaire.Results: A statistical test is conducted using SPSS, the FisherExact test, which shows that P = 0.001 < α = 0.05, where the hypothesis is accepted which means there is a significant link between family support and the readiness of the menarche in the young womenConclusion: There is a relationship between family support and readiness to target because of the provision of good family support so that the young women have a mental knowledge and strengthening to confront the menarche. It is hoped that the family will pay more attention to the children when they begin to step up, especially when the young women are ready to face the menarche. Keywords: Family support, menarche readiness, young women